Characterization, number, and spatial organization of nerve fibers in the human cervical vagus nerve and its superior cardiac branch - Bettina Kronsteiner; Genova Carrero-Rojas; Lukas F. Reissig; Atieh Seyedian Moghaddam; Karoline M. Schwendt; Sylvia Gerges; Udo Maierhofer; Oskar C. Aszmann; Angel M. Pastor; Attila Kiss; Bruno K. Podesser; Wolfgang Birkfellner; et al. (Brain Stimulation, 2024)
Background: Electrical stimulation of the vagus nerve (VN) is a therapy for epilepsy, obesity, depression, and heart diseases. However, whole nerve stimulation leads to side effects. We examined the neuroanatomy of the mid-cervical segment of the human VN and its superior cardiac branch to gain insight into the side effects of VN stimulation and aid in developing targeted stimulation strategies. Methods: Nerve specimens were harvested from eight human body donors, then subjected to immunofluorescence and semiautomated quantification to determine the signature, quantity, and spatial distribution of different axonal categories. Results: The right and left cervical VN (cVN) contained a total of 25,489 ± 2781 and 23,286 ± 3164 fibers, respectively. Two-thirds of the fibers were unmyelinated and one-third were myelinated. About three-quarters of the fibers in the right and left cVN were sensory (73.9 ± 7.5 % versus 72.4 ± 5.6 %), while 13.2 ± 1.8 % versus 13.3 ± 3.0 % were special visceromotor and parasympathetic, and 13 ± 5.9 % versus 14.3 ± 4.0 % were sympathetic. Special visceromotor and parasympathetic fibers formed clusters. The superior cardiac branches comprised parasympathetic, vagal sensory, and sympathetic fibers with the left cardiac branch containing more sympathetic fibers than the right (62.7 ± 5.4 % versus 19.8 ± 13.3 %), and 50 % of the left branch contained sensory and sympathetic fibers only. Conclusion: The study indicates that selective stimulation of vagal sensory and motor fibers is possible. However, it also highlights the potential risk of activating sympathetic fibers in the superior cardiac branch, especially on the left side.